The esophagointestinal anastomosis - Cendán Alfonzo, Juan E (Cirugía del Uruguay, 1974)
Total gastrectomy is defined as the operation which removes the entire stomach including . cardias and pylorus. Issues are referenced that implies its realization and insists that the operative risk deserves special consideration. East is fundamentally linked to the removal of the cardias and especially to the anastomosis esophagointestinal